Evaluating the benefit of early patient and public involvement for product development and testing with small companies - Elanor C. Hinton; Cameron Fenwick; Martin Hall; Mike Bell; Julian P. Hamilton‐Shield; Andrew Gibson (Wiley, 2023)
Abstract Introduction There is a growing understanding of the benefits of patient and public involvement (PPI), and its evaluation, in research. An online version of the CUBE PPI evaluation framework has been developed. We sought to use the CUBE to evaluate the value of early PPI with two small healthcare companies during product development. Methods Contributors were recruited online and had lived experience of either type 1 diabetes or obesity. Two 1‐h sessions were run with a company developing a smartphone application to manage diabetes (DEE‐EM): one with young people (YP; n = 5) and one with parents (n = 7). Two 1‐h sessions were run with a company developing a weight‐loss product, both with adults (n = 7 in each session). Sessions were facilitated by an independent University researcher and attended by company representatives, who presented their product. One facilitator led the evaluation of the session by giving a demonstration of the CUBE and asking simple questions in the YP session. Results A high proportion of contributors completed the CUBE (80.5% DEE‐EM; 93% Oxford Medical Products). Responses were positive to all four CUBE dimensions (in italics). Contributors felt there were diverse ways to contribute to the sessions, and that they had a strong voice to add to the discussion. Balance was achieved regarding whose concerns (public or company) led the agenda, and contributors felt that both companies would make changes based on the discussion. The supportive attitude of both companies resulted in most contributors feeling comfortable participating in PPI sessions with the industry, while recognising the profit‐making aspect of their work. Conclusions PPI with small healthcare companies is both feasible and worthwhile. The CUBE framework facilitated the evaluation of the interaction between experts in different knowledge spaces. We provide recommendations for future projects, including considerations of who should participate and the level of implicit endorsement of the product that participation implies. Patient or Public Contribution People with lived experience of type 1 diabetes or obesity were invited to contribute to one of four PPI sessions, which they then evaluated. One contributor agreed to contribute to the analysis of the evaluation data and interpretation and preparation of the manuscript.